Ethnomedicinal uses of plants in the treatment of paediatric geohelminth infections in Kalat district of Northern Balochistan, Pakistan. (13th May 2016) - Bibi, Tahira; Ahmad, Mushtaq; Edwards, Sarah E.; Tareen, Niaz Mohammad; Jabeen, Rukhsana; Abdullah, Irum
Abstract: Ethnopharmacological relevance: Infection by intestinal parasitic worms (soil-transmitted helminths or geohelminths) is prevalent in many parts of the world, and poses a particular health risk to children. This paper presents findings from a preliminary study with the primary aim to document indigenous knowledge about the use of herbal medicines in the treatment of intestinal worm infections in children among the local communities of Kalat district of northern Balochistan, Pakistan. Materials and methods: Ethnomedicinal data were collected through a triangulation approach, that included participant-observation and rapid appraisal methods. Prior-informed consent (PIC) was obtained from participants before conducting structured and semi-structured interviews and delivering an open ended questionnaire. A total of 94 participants, including 28 men (of whom 7 were traditional healers), and 66 women of four different age groups were interviewed. Results were analyzed using quantitative indices of Use Value citations (UVC) and Disease-Consensus Index (DCI). Results: Fewer men than women agreed to be interviewed, thus overall women in the area appeared to have more ethnomedicinal knowledge. The majority of study participants belonged to the older age group (>55 years). A total of 49 plant species, belonging to 47 genera, distributed in 30 families were reported. The families Asteraceae and Lamiaceae were most frequently represented, with four species each. Trees were the most common life form, with seeds the most frequently cited plant part used (29%). Nearly a third (31%) of plant-based remedies reported in the treatment of intestinal worms were administered as a decoction. The highest UVC and DCI was reported for the species Ferula assa-foetida sL. (UVC 0.51, DCI 0.46). Conclusions: This study provides previously unreported data on the use of medicinal plants in the treatment of geohelminth infections in children of Kalat. Eight species, Acacia modesta Wall ., Asparagus capitatus Baker, Microcephala lamellata (Bunge) Pobed., Nepeta praetervisa Rech.f., Plantago ciliata Desf., Pistacia atlantica Desf., Seriphidium quettense (Podlech) Y.R.Ling and Thymus linearis Benth. are reported here as anthelmintics for the first time. Detailed studies on the anthelmintic activity of chemical constituents of these species are lacking from existing literature. Further phytochemical, pharmacological and toxicity studies are required in order to evaluate the efficacy and safety of these newly reported anthelmintic species. These plants may provide a source of novel anthelmintic drug leads, which are urgently required due to the problem of global anthelmintic resistance. Graphical abstract: